Domestic Violence (KDRT) in the Perspective of Islamic Criminal Law - Zulfahmi, Zulfahmi (PT. Ratu Bilqis Azzahira bekerjasama dengan Fakultas Syariah Universitas Islam Zainul Hasan Probolinggo, 2024)
Domestic violence is not only experienced by women. However, based on everyday facts, women tend to be more vulnerable and often become victims of violence in their families. Therefore, Islam strictly prohibits and provides strict sanctions against perpetrators of domestic violence. The purpose of this writing is to examine domestic violence (KDRT) according to Islamic criminal law and to correlate it with Indonesian positive law. The method in this research is library research, collecting data sourced from the Al-Qur'an, Hadith, scriptures, books, journals and other library materials that discuss domestic violence. The results of this research show that in Islamic criminal law, acts of domestic violence (KDRT) are considered a form of crime and acts that are prohibited by the Shari'a because they can cause harm and endanger the safety of wives and children. This action falls into the category of jarimah . From a legal perspective, perpetrators of criminal acts of physical violence against women and children can be subject to prison sentences and fines. According to a criminal law perspective Islam regarding domestic violence, in substance the legal action domestic violence crime, especially physical violence against wives in the PKDRT Law is part from the action of jarimah , namely no punishment for other than life. Related with a prison sentence PKDRT Law according to criminal law Islam, so this criminal act is classified as ta'zir.